EFFECT OF ETHEPHON CONCENTRATION AT DIFFERENT GROWTH STAGES ON YIELD AND ITS COMPONENTS OF WHEAT - & Hashim, Al-Naqeeb (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
An experiments were carried out at the field of Crops Dept., Coll. of Agric., Univ. of Baghdad, Abu Ghraib during 2010-2011 and 2011-2012 seasons to study effect of foliar stages and concentrations of ethephon on some growth traits and the yield of wheat (Triticumaestivum L.) Abu Ghraib-3 var. A split plot arrangement according to RCBD was used with four replications. The main plots were spray ethephon with four stages according to Zadok’s scale which is: one leaf throught the sheath (ZGS10), three leaves unfolded stage (ZGS13), elongation stage (ZGS30) and flag leaf ligue visible (ZGS39), and the sub-plots was ethephon spray with three concentrations (0.400, 0.600 and 0.800) Kg.ha-1 in addition to control treatment. The results showed that ZGS13 gave lowest mean for height plant (90.47 and 92.80) cm, while ZGS30 was superior in number of tillers (493.61 and 535.35) tiller.m-2, percentage of tillers carried of spike (78.83 and 81.21, number of spikes (389.64 and 636.80) spike.m-2, grain yield (4.07 and 4.32) ton.ha-1, biological yield (11.29 and 11.59)ton.ha-1 and harvest index (36.03 and 37.26)% for both seasons, respectively. Also, the results showed that 0.800 Kg.ha-1 produced lowest means for height plant (77.91 and 86.25) cm and lodging index (3.65 and 2.75), and this treatment (0.800 mg.L-1) gave highest means for number of tillers (499.22 and 540.99) tiller.m-2, percentage of tillers carried of spike (78.88 and 78.15)%, number of spikes (393.84 and 423.91) spike.m-2, grain yield (4.14 and 4.12) ton.ha-1, biological yield (11.47 and 11.70)ton.ha-1 and harvest index (36.11 and 37.62)% for both seasons, respectively. The interaction between ZGS30 and 0.400 Kg.ha-1ethephon gave highest percentage of tillers carried of spike (80.96%) in the first season only.